Formononetin ameliorates muscle atrophy by regulating myostatin‐mediated PI3K/Akt/FoxO3a pathway and satellite cell function in chronic kidney disease. Issue 3 (6th January 2021) - Liu, Lingyu; Hu, Rong; You, Haiyan; Li, Jingjing; Liu, Yangyang; Li, Qiang; Wu, Xiaohui; Huang, Jiawen; Cai, Xiangsheng; Wang, Mingqing; Wei, Lianbo
Abstract: Muscle atrophy is a common complication in chronic kidney disease (CKD). Inflammation and myostatin play important roles in CKD muscle atrophy. Formononetin (FMN), which is a major bioactive isoflavone compound in Astragalus membranaceus, exerts anti‐inflammatory effects and the promotion of myogenic differentiation. Our study is based on myostatin to explore the effects and mechanisms of FMN in relation to CKD muscle atrophy. In this study, CKD rats and tumour necrosis factor α (TNF‐α)‐induced C2C12 myotubes were used for in vivo and in vitro models of muscle atrophy. The results showed that FMN significantly improved the renal function, nutritional status and inflammatory markers in CKD rats. Values for bodyweight, weight of tibialis anterior and gastrocnemius muscles, and cross‐sectional area (CSA) of skeletal muscles were significantly larger in the FMN treatment rats. Furthermore, FMN significantly suppressed the expressions of MuRF‐1, MAFbx and myostatin in the muscles of CKD rats and the TNF‐α‐induced C2C12 myotubes. Importantly, FMN significantly increased the phosphorylation of PI3K, Akt, and FoxO3a and the expressions of the myogenic proliferation and differentiation markers, myogenic differentiation factor D (MyoD) and myogenin in muscles of CKD rats and the C2C12 myotubes. Similar results were observed in TNF‐α‐induced C2C12 myotubes transfected with myostatin‐small interfering RNA (si‐myostatin). Notably, myostatin overexpression plasmid (myostatin OE) abolished the effect of FMN on the phosphorylation of the PI3K/Akt/FoxO3a pathway and the expressions of MyoD and myogenin. Our findings suggest that FMN ameliorates muscle atrophy related to myostatin‐mediated PI3K/Akt/FoxO3a pathway and satellite cell function.